Assessing Romania's progress towards Sustainable Development Goals 8, 9, 10 and 12: a comparative analysis in the EU context - Irina Puiu (Journal of Research and Innovation for Sustainable Society)
The concept of sustainable development, as introduced in the 1987 Brundtland Report and globally formalized through the United Nations' 2030 Agenda, has become a cornerstone for addressing economic, social, and environmental challenges worldwide. This article provides an in-depth analysis of Romania’s progress in achieving four key Sustainable Development Goals (SDGs): SDG 8 (Decent Work and Economic Growth), SDG 9 (Industry, Innovation, and Infrastructure), SDG 10 (Reduced Inequalities), and SDG 12 (Responsible Consumption and Production). Using data from the National Institute of Statistics of Romania, this study evaluates the country’s performance by comparing it to the European Union average, top international performers, and economies with similar profiles. The analysis covers a range of indicators, including employment rates, industrial innovation, income inequality, and environmental sustainability, shedding light on Romania’s strengths and weaknesses in these areas. Romania has made notable progress in reducing unemployment and increasing gross national income per capita, contributing to positive trends in economic growth. However, significant challenges remain in the areas of industrial innovation, reducing inequalities, and achieving more sustainable consumption and production patterns. The findings reveal that while Romania is moving towards its 2030 targets, gaps persist, particularly in aligning with EU benchmarks on social inclusion and environmental responsibility. This study highlights the need for continued policy interventions, greater investment in research and innovation, and stronger public-private partnerships to accelerate Romania’s progress toward sustainable development. The article concludes with policy recommendations aimed at enhancing Romania’s ability to meet its 2030 SDG commitments, ensuring a more equitable and sustainable future